Księga Arystotelesa o dyspozycjach dianoetycznych (intelektualnych) „Etyka nikomachejska” VI - Wesoły, Marian Andrzej (Filozofia Publiczna i Edukacja Demokratyczna, 2019)
The article concerns book VI of Aristotle’s Nicomachean Ethics on the integrated approach to the dianoetic (intellectual) dispositions in the field of thinking, action and production, with the leading con-cept of phronesis as practical wisdom. We propose here a new Polish translation of this book in a rendition as close to the Greek original as possible. For the sake of clarity, we highlight the chapters with vari-ous appropriate thematic headings. The introductory note is intended to prepare the reader for the difficult text that teems with important conceptual distinctions and sophisticated lines of argument.